DENTIN HYPERSENSITIVITY ASSOCIATED WITH NON-CARIOUS CERVICAL LESIONS: A LITERATURE REVIEW - Tarcyla Pereira de Carvalho; Lucas Mendes Gabri; Victor Gila Gomes de Mattos; Marcela Melo dos Santos; Luis Paulo Diniz Barreto (Portal de Periódicos da Marinha do Brasil, 2020)
The aim of this study was to present a literature review on the etiology, diagnosis and treatment of dentin hypersensitivity. Dentin hypersensitivity is characterized by short and acute pain, which arises from exposed dentin in response to stimuli, typically thermal, evaporative, tactile, osmotic or chemical and which cannot be attributed to any other dental defect or pathology. The term "Root Hypersensitivity" is used to describe the dentin hypersensitivity normally associated with gingival recessions, abrasions, erosions and abfractions. The etiology is multifactorial and the choice of the ideal treatment depends on a correct diagnosis. Other entities related to hypersensitivity are non-carious cervical lesions (NCCL), which are common conditions in a more distant society with new habits. All treatments presented, such as the use of blocking agents associated with desensitizing toothpaste, restorative procedures, the use of lasers and surgical procedures are effective in reducing dentinal hypersensitivity. An evaluation of the periodontal profile is also important especially when aiming at marginal stability and prevention of possible future NCCL. Thus, it can be concluded that dentin hypersensitivity and non-carious cervical lesions are conditions that require the dentist's knowledge in relation to their etiology, forms of treatment and long-term maintenance.